Tantangan Saham Syariah Di Pasar Global - Arifin, Desi Siti Habibah; Prasetyo, Yoyok (Universitas Madura, 2025)
The development of Islamic financial markets has shown significant growth. Islamic stocks have become one of the investment instruments that investors are increasingly interested in. Despite this growth, Islamic stocks face complex challenges in the global market. This research is a type of qualitative literature research with descriptive analysis method. Data sources come from written literature, such as books, scientific articles, and others related to the research subject. The challenges of Islamic stocks include limited financial instruments that comply with sharia principles, lack of awareness and understanding of Islamic stocks among global investors, and differences in regulation and compliance in various countries. In addition, low liquidity, complexity in the valuation of Islamic stocks, and changing interpretations of sharia by religious authorities add another layer of difficulty for investors. Lack of supporting infrastructure and global market volatility are also factors that affect the attractiveness of Islamic stocks.